Formation and development of Staphylococcus biofilm: With focus on food safety. Issue 4 (14th March 2017) - Miao, Jian; Liang, Yanrui; Chen, Lequn; Wang, Wenxin; Wang, Jingwen; Li, Bing; Li, Lin; Chen, Dingqiang; Xu, Zhenbo
Abstract: Staphylococcus is a common gram‐positive pathogen, which has been considered to be a leading concern to public health and food safety due to the multi‐drag resistance and virulence. As is known, most Staphylococcus tend to form biofilm both during various food processing procedures and in environment, and the bacteria in biofilms show a number of specific advantages over planktonic bacteria due to strong resistance ability. As a consequence, inhibition and removal of Staphylococcus biofilm is difficult for food safety during processing. The present review aims to discuss and demonstrate the formation and development of Staphylococcus biofilm based on food safety account under the background of both phenotype and genetic regulation, providing scientific reference for control strategy. Practical application: As a common foodborne pathogen, Staphylococcus aureus in food industry is a potential harm to the health of both customer and stuff. Biofilm plays a significant role in bacterial survival, tolerant to environmental stresses. Thus, a comprehensive understanding of biofilm is of essential and urgent need. This review of biofilm of Staphylococcus aureus illustrated the biofilm in food industry and its formation, influential factor, quantification, genetic regulation mechanism, and control strategies, which provided a background of Staphylococcus aureus biofilm prevention in food industry.